6-hour Training in click-based echolocation changes practice in visual impairment professionals - Thaler, Lore; Di Gregorio, Giammarco; Foresteire, Denise (Frontiers in Rehabilitation Sciences, 2023)
Click-based echolocation can support mobility and orientation in people with vision impairments (VI) when used alongside other mobility methods. Only a small number of people with VI use click-based echolocation. Previous research about echolocation addresses the skill of echolocation per se to understand how echolocation works, and its brain basis. Our report is the first to address the question of professional practice for people with VI, i.e. a very different focus. VI professionals are well placed to affect how a person with VI might learn about, experience or use click-based echolocation. Thus, we here investigated if training in click-based echolocation for VI professionals might lead to a change in their professional practice. The training was delivered via 6-hour workshops throughout the UK. It was free to attend, and people signed up via a publicly available website. We received follow-up feedback in the form of yes/no answers and free text comments. Yes/no answers showed that 98% of participants had changed their professional practice as a consequence of the training. Free text responses were analysed using content analysis, and we found that 32%, 11.7% and 46.6% of responses indicated a change in information processing, verbal influencing or instruction and practice, respectively. This attests to the potential of VI professionals to act as multipliers of training in click-based echolocation with the potential to improve the lives of people with VI. The training we evaluated here could feasibly be integrated into VI Rehabilitation or VI Habilitation training as implemented at HEIs or CPD.